Consumer protection act No. 35 of 2019 - Sanjeev, Muthuswamy Brinda (Chennai Swamy, 2023)
This Act as promulgated in 1986 was enacted to provide for better protection of the interests of consumers and for that purpose to make provisions for the establishment of consumer councils and other authorities for the settlement of consumer disputes and matters connected therewith.
Keywords: Act